A Case Study of African American Parental Involvement in an Urban Middle School - Antonioli, Luca (Frontiers in pharmacology, 2016)
Studying parental involvement offers the opportunity to develop new strategies and resources to increase involvement at the middle schools serving a similar demographic population. In a large economically disadvantaged urban middle school in the southeastern United States, very little parental involvement occurs from the African American population. The purpose of this qualitative single case study was to examine African American parents' perception about their involvement in their middle school students' education. Guided by Epstein, Simon, and Salinas' parental involvement model, which describes 6 levels of parental involvement, the research questions guiding this project study examined African American parents' perceptions about middle school children's educational experiences, the level of parental involvement in middle school education, and parental beliefs about student success. A purposeful participant pool of 10 African American parents of Grade 7 and 8 students was used for data collection. Ten parents completed the preliminary paper questionnaire, 10 parents participated in 1-on-1 semi-structured interviews, and 7 parents participated in a focus group discussion. Thematic analysis of data followed the open coding process and identified categories and themes. The findings suggested the need for a parent education program involving the use of new strategies and resources for increasing African American parent involvement at the middle school level. Social change will occur by empowering African American parents to be involved in their middle school students' education